Evaluation of Anticancer, Antibacterial and Haemolytic Activities of Crude Mucus from Marine Catfish Tachysurus Dussumieri: Life Sciences-Zoology for Novel drug discovery - Kavitha Raja; Tharun Jayakumar; Gracy Jenifer Sahayanathan; Deepakrajasekar Padmanaban; Kathirvel Neelan; Arulvasu Chinnasamy (International Journal of Life Science and Pharma Research, 2022)
Marine organisms are one of the diverse groups of animals that are highly specialized for their aquatic existence. The skin mucus share protective activities against environment that are rich in infectious agents. The current study aims to analyses the anticancer, antibacterial and haemolytic properties of crude epidermal mucus from marine catfish Tachysurus dussumieri. Cell viability and Cytotoxcity was assessed by MTT method on HT 29 (human colon carcinoma) and Vero (kidney epithelial cells of African Green Monkey) cell line. In Vero up to 1000 µg/ml of crude mucus shows cell viability of 80% and hence mucus concentration for treatment of HT 29 cells was fixed between100 to 1000 µg/ml. The proliferation inhibition on HT 29 at a concentration of 400µg/ml mucus from T. dussumieri at 24 h. Cellular and nuclear morphological variations was observed in different concentration of mucus, followed by DNA fragmentation to confirm the induction of apoptosis. Moreover, mucus sample was tested against Gram positive and negative bacteria, The maximum zone of inhibition was observed in S. aureus (15.61 ± 0.7 mm), followed by B. subtilis (8.32 ± 0.32 mm) and E. coli (8.14 ± 0.08 mm). Interestingly mucus from T. dussumieri showed haemolytic activity on different blood samples of goat, rat, sheep, buffalo, rabbit , cow, hen and human. Mucus showed maximum haemolytic activity against goat, rat, sheep and buffalo when compared to other RBCs. All these results showed that the epidermal mucus has more efficacy on therapeutic application in near future..